Estudo da comunidade de pequenos mamíferos não-voadores, sob efeito do fogo e da borda, em área de floresta de transição Amazônia-Cerrado, Querência, MT - SANTOS, Paulo Guilherme Pinheiro dos (Universidade Federal do Pará, 2013)
The deforestation of the Amazon, caused by farming and agribusiness activities in the northern state of Mato Grosso, has committed Transition Forests Amazon-Savanna, before the biodiversity of these areas is known by researchers. The fauna of small non-flying mammals is part of the little-known groups in the region, and may be suffering impacts of human activities, primarily effect of fire, used for cleaning of pastures and deforestation for the soybean plantations. This study characterized the diversity of small mammals not flying in an area of Amazon forest-savannah transition in the northern state of Mato Grosso and investigated the effect of fire and the effect of edge on this group of fauna. Two areas of 150 hectares were sampled, a preserved and another under impact of fire, with 183 traps of the type live-trap for three years in two season (dry and rainy seasons). The method used was the capture-mark-recapture. The sampling effort was 23,424-traps night. 390 individuals were captured with a successfully capture of 1.66%. A total of 11 species were caught, 6 rodents and 5 marsupials. Hylaeamys megacephalus was the most abundant species. The diversity of small mammals in the study area was more related to the Savanna than Amazon. In relation to fire, the species richness was not statistically different, but the abundance was significantly higher in transects located in an area without fire. Two distinct groups of transects were characteristic depending on the presence or absence of fire based on the composition of small mammals. The abundance of Hylaeamys megacephalus was significantly higher in transects that suffered no impact from fire. Regarding the effect of edge in Area 2, despite the richness of species was not significantly different, the abundance was significantly higher regarding distance from the border. Already in Area 1, nor richness nor abundance was statistically different regarding distance from the edge. This fact could be masked by both the direct and indirect effect of experimental fire on small mammals. When considered together fire and distance from the border, the relationship between them became clearer, since all transects sampled under effect of the fire had minor abundances. The population size of Hylaemys megacephalus was calculated over five seasons (dry and wet) in the area without influence of fire, and the rainy season of 2006 was statistically different peak and the other that growth can be explained by the “Alle effect”. There was no statistically significant differences in the structure of the community of small non-flying mammals between the dry and rainy seasons. This work contributed to the search of mammal knowledge at this region threatened by human pressures.